Types of Assimilation in English as Recognized by Iraqi EFL Learners at the University Level : A Perceptual Study - Furqan Abdul-Ridha Kareem Altaie ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The main problem of this research paper is that students of English find difficulties in recognizing types of assimilation . This current paper aims at assessing the students’ capacity to handle the three main types of assimilation through listening to certain phrases and sentences . The results showed that the participants have a lot of difficulties in recognizing the types of assimilation. The findings are discussed in the view of statistical analysis. DOI /10.54633/2333-021-042-035